Perbedaan Motivasi Kerja Generasi Milenial Berstatus Sosial Ekonomi Rendah di Kota Makassar - Hasmy, Zulfauzy Abu; Riyono, Bagus (Flourishing Journal, 2025)
Millennial workers are a group of individuals who are relatively new to the workforce and have limited experience. Nevertheless, they have rapidly grown to dominate the job market. Several previous studies have explored the various work motivations of the millennial generation, which have since sparked ongoing debates. The purpose of this study is to examine and describe the differences in work motivation among Millennials with low socioeconomic levels in Makassar. This study hypothesizes that simultaneously there is a significant difference in the Millennials’ work motivation based on the personal need fulfillment of Millennials workers in Makassar. The participants in this study are 200 millennial workers with a low economic level. They are consisted of work focused in the service sector, employees in the production sector, sales workers, and fishermen. The Work Motivation Scale is used for data collection by an online platform and a paper-and-pencil test. Moreover, the difference test in the multivariate analysis of variance (MANOVA) is generated in this research. The result shows that, simultaneously, there is a significant difference in the work motivation based on personal need fulfilment of the Millennials who have low economic level in Makassar. AbstrakKelompok pekerja generasi milenial merupakan mereka yang baru serta minim pengalaman yang memasuki dunia kerja. Meskipun demikian perkembangan mereka sangat cepat dalam mendominasi lapangan pekerjaan. Beberapa studi terdahulu menjelaskan berbagai motivasi kerja generasi milenial yang kemudian menjadi perdebatan. Penelitian ini bertujuan untuk menguji dan mendeskripsikan perbedaan motivasi kerja pada generasi milenial berstatus sosial ekonomi rendah di Kota Makassar. Hipotesis penelitian ini adalah secara simultan terdapat perbedaan yang signifikan pada motivasi kerja berdasarkan pemenuhan kebutuhan pada pekerja milenial di Kota Makassar. Partisipan dalam penelitian ini sebanyak 200 orang pekerja milenial berstatus sosial ekonomi rendah yang bekerja pada bidang pekerjaan pelayanan jasa, industri dan pengolahan, tenaga penjualan serta nelayan tangkap. Pengumpulan data menggunakan skala motivasi kerja yang disebar pada platform online serta dengan cara paper and pencil test. Analisis data menggunakan uji perbedaan multivariat analysis of varians (Manova). Hasil analisis menunjukkan bahwa terdapat perbedaan yang signifikan pada motivasi kerja berdasarkan pemenuhan kebutuhan pada pekerja milenial berstatus sosial ekonomi rendah di Kota Makassar.